Tourism Service Promotion Strategy in Aek Sijorni Tourism Development in Padang Sidempuan City (International Journal of Cultural and Social Science, 2023)
Indonesia is an archipelagic country that is beautiful and rich in natural and cultural wealth. It is proven that Indonesia’s natueal wealth is an attraction so that it invites foreign and local tourists to visit and enjoy it. This is then used bt the goverment and the community to become an economic resource. In this case, promotional communication strategis play an important role in selling the nuances of Indonesia’s natural beauty to attract tourist. In the case, the researcher is interested in further researching how the local community or goverment can promot the Aek Sijorni spot to tourist.